The strategic partnership between the European Union, Latin America and the Caribbean : a joint commitment (Office for Official Publications of the European Communities LuxembourgLU, 2008)
Sets out the framework of the strategic partnership, and presents the background and the most recent developments.
Keywords: PARTNERSHIP